Manajemen Zakat Produktif dalam Upaya Meningkatkan Kesejahteraan Ekonomi Masyarakat - Muhammad Reza Atqia (Tadbir: Jurnal Manajemen Dakwah, 2018)
This research discusses about management of zakat in an effort to improve the economic welfare of the community carried out by the Rumah Zakat from the beginning planned, implemented and supervised the program to achieve that goal.. This study uses the deskiptive method, which in conducting this research, the researcher tries to describe and describe the condition of the object of research based on facts that are visible or as they are. The results obtained by this study, namely the activities of Zakat Houses in managing productive zakat, Rumah Zakat moves based on its vision and mission and moves by always running partnerships with various parties, both the community and the government. Zakat House also has the planning, implementation and supervision of good productive zakat for the economic welfare of the community. This is given to small entrepreneurs in order to develop their business to become more productive.